2017
DOI: 10.1155/2017/4876494
|View full text |Cite
|
Sign up to set email alerts
|

Giant Perineal Solitary Fibrous Tumor: A Rare Case Report

Abstract: Background. Solitary fibrous tumor (SFT) is a fibroblastic mesenchymal tumor that was initially described from the pleura but currently arises at almost every anatomic site. It is usually benign, and surgical resection is curative. SFT involving the perineum is extremely rare. This is the third case report of a perineal SFT in the literature. Case Presentation. We reported an uncommon case of a 64-year-old man presenting with a huge perineal mass that started growing 3 years before his arrival in our service. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 18 publications
(19 reference statements)
1
10
0
Order By: Relevance
“…However, a perineal location is rare, and to our knowledge, our case is the 4 th reported in the literature. Suster et al, Kim et al, and de Souza Melo et al have reported similar observations [ 4 ]. Therefore, this case report is interesting and useful to avoid misdiagnosis and achieve early treatment.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…However, a perineal location is rare, and to our knowledge, our case is the 4 th reported in the literature. Suster et al, Kim et al, and de Souza Melo et al have reported similar observations [ 4 ]. Therefore, this case report is interesting and useful to avoid misdiagnosis and achieve early treatment.…”
Section: Discussionsupporting
confidence: 52%
“…Our research revealed more reported cases that refer to the same condition and anatomic region under different names. In this study, we have included all reported cases of perineal, peri-anal, ischiorectal fossa, and ischioanal fossa SFTs ( Table 1 ) [ 4 , 6 , 9 18 ]. We excluded cases of pelvic, retroperitoneal, and urinary tract SFTs from our review given the notable differences in their diagnostic and treatment strategies, including the surgical approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in electron microscopy and immunohistochemistry have demonstrated a mesenchymal rather than a mesothelial origin of SFTs. While the majority of SFTs occur within the pleura, approximately 30% of SFTs arise in the peritoneal cavity, retroperitoneal soft tissue, and pelvis [ 1 , 2 ]. However, SFTs occurring in the ischiorectal fossa are extremely rare.…”
Section: Case Presentationmentioning
confidence: 99%
“…In unresectable cases, surgical cytoreduction with chemotherapy and radiation therapy might be useful [ 20 , 21 ]. There is no consensus concerning follow-up for SFTs, but continued long-term surveillance is advised due to the indolent nature of the tumor and the possibility of late recurrence up to 20 years after initial treatment [ 1 , 2 ].…”
Section: Case Presentationmentioning
confidence: 99%